2017
DOI: 10.1371/journal.pone.0179981
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and correlation of cytokine-specific autoantibodies with epidemiological factors and C-reactive protein in 8,972 healthy individuals: Results from the Danish Blood Donor Study

Abstract: Natural cytokine-specific autoantibodies (c-aAb) have been measured in healthy and diseased individuals, and have been considered as both endogenous immune-regulators and pathogenic factors. Overall, the etiology and potential pathology of c-aAb are still undefined. To further characterize the sero-prevalence, predictors and consequences of high c-aAb levels, we performed the largest population-based study of c-aAb to date, using participants and epidemiological data from the Danish Blood Donor Study. Using a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
40
1
3

Year Published

2020
2020
2022
2022

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 30 publications
(53 citation statements)
references
References 55 publications
7
40
1
3
Order By: Relevance
“…In line with prior studies [16], we found c-aAb levels to be associated with sex and age, as well as a novel association of IL-6 c-aAb and oral contraceptives. As such, we observed a strong sex interaction for c-aAb and our investigated outcomes.…”
Section: Discussionsupporting
confidence: 91%
See 4 more Smart Citations
“…In line with prior studies [16], we found c-aAb levels to be associated with sex and age, as well as a novel association of IL-6 c-aAb and oral contraceptives. As such, we observed a strong sex interaction for c-aAb and our investigated outcomes.…”
Section: Discussionsupporting
confidence: 91%
“…GM-CSF c-aAb have also been associated with multiple variants of opportunistic infections [30], and here we observed high levels of c-aAb to be associated with an increased risk of sulfonamide prescriptions in women. Interestingly, despite the previously observed association between IL-6 c-aAb and low levels of CRP [16], high levels of IL-6 c-aAb did not predict higher or lower risk of filing prescriptions in this study, which may reflect the pleiotropic roles of IL-6 as both a pro-and antiinflammatory cytokine [31]. Furthermore, c-aAb have in some reports been observed to act as agonists of their target cytokine function [32], adding further complexity to our findings.…”
Section: Discussioncontrasting
confidence: 60%
See 3 more Smart Citations